2005
DOI: 10.1016/s0753-3322(05)80029-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamines: follow-up on 10-year study in health and cardiovascular disease

Abstract: The predictive value of blood pressure (BP), heart rate (HR), and catecholamines in terms of any subsequent development of cardiovascular disease was investigated. Systolic (S) and diastolic (D) BP, HR, epinephrine (E) and norepinephrine (NE) were measured three times a year in 1980, 1984, and 1989 on 20 clinically healthy subjects, 18 patients with 'essential hypertension', and 22 patients with angina pectoris. Of the 22 patients in the latter group, 15 died during a 2-year follow-up (1990)(1991). Each indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In this study, we found a strong positive correlation between the quantitative measures and subjective stress scales for dopamine and the primary metabolite 3 MT as well as a strong inverse correlation with epinephrine. The findings suggest that work conditions may be important regulators of the sympathetic tone and thereby significant modifiers of cardiovascular disease risk [12,40,41], mental health [42,43], and metabolic disorders such as diabetes [15,24] and obesity [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found a strong positive correlation between the quantitative measures and subjective stress scales for dopamine and the primary metabolite 3 MT as well as a strong inverse correlation with epinephrine. The findings suggest that work conditions may be important regulators of the sympathetic tone and thereby significant modifiers of cardiovascular disease risk [12,40,41], mental health [42,43], and metabolic disorders such as diabetes [15,24] and obesity [26].…”
Section: Discussionmentioning
confidence: 99%